Implementation of Thematic Learning Curriculum 2013; Multi Site Study at MIN 2 Kediri and MIN 1 Kediri City - Sri Ambarwati (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
Abstract This paper intends to answer the implementation of thematic learning in the 2013 curriculum. In addition, the authors examine the factors that support and obstruct the implementation of thematic learning in the 2013 curriculum. The type of research used is descriptive qualitative using interview, observation and documentation techniques. The research was conducted at 2 MIN in Kediri City. The results of the first study, Thematic Learning has a very important role in increasing students’ attention, learning activities, and understanding of the material being studied, because learning is more student-centered, provides direct experience to students, the separation of subjects is not very clear, presents concepts from various Subjects in a learning process, are flexible, learning outcomes can develop according to student interests and needs. Thematic learning to be successful is carried out by taking the stages of planning, implementation, and evaluation. Second, the supporting factors include: (a) infrastructure, (b) the existence of a remedial teaching program, (c) the existence of training on the 2013 curriculum, (d) teacher creativity, (e) use of appropriate methods, (f) the existence of ice breaking in learning. meanwhile, inhibiting factors in the implementation of thematic learning in the 2013 curriculum include: (a) internal students, (b) teachers do not understand the 2013 curriculum, (c) teachers are less creative in collaborating learning methods, (d) lack of parental support, ( e) less supporting infrastructure, and (f) no previous training.